Parental pre‐pregnancy BMI is a dominant early‐life risk factor influencing BMI of offspring in adulthood. - S. R. Rath; J. A. Marsh; J. P. Newnham; K. Zhu; H. C. Atkinson; J. Mountain; W. H. Oddy; I. P. Hughes; M. Harris; G. M. Leong; A. M. Cotterill; P. D. Sly; et al. (Wiley, 2016)
Summary Objective We examined parental and early‐life variables in order to identify risk factors for adulthood overweight and obesity in offspring. We report here on the longitudinal prevalence of overweight and obesity in Australian children born between 1989 and 1991 and followed from birth to age 22. Methods Data were analysed on 1355 participants from the Western Australian Pregnancy Cohort (Raine) Study, with anthropometry collected during pregnancy, at birth, one year and at three yearly intervals thereafter. Multivariate analyses and cross‐sectional logistic regression quantified the timing and contribution of early‐life risk factors for overweight and obesity in young‐adulthood. Results At five years of age 12.6% of children were overweight and 5.2% were obese. By early adulthood, the prevalence of obesity had increased to 12.8%, whilst overweight remained relatively stable at 14.2% (range from early childhood to adulthood 11-16%). Parental pre‐pregnancy body mass index (BMI) was the strongest determinant of adult offspring BMI. Although rapid first year weight gain was associated with increased offspring BMI, the impact of first year weight‐gain diminished over childhood, whilst the impact of parental BMI increased over time. Conclusions Parental pre‐pregnancy BMI and rapid early‐life weight gain predispose offspring to obesity in adulthood.